The effect of cobalt substitution on structure and magnetic properties of nickel ferrite - Nguyen, Khanh Dung (H. : ĐHQGHN, 2017)
A series of cobalt doped nickel ferrite with composition of Nii.xCoxFe204 with X ranges I'roni 0.0 to 0.8 (in steps of 0.2) was prepared by using co-precipitation method and subsequently sintered, annealed at 600“c for 3h. The influence of the Co-content on the crystal lattice parameter, the stretching vibration and the magnetization of specimens were subsequently studied. XRD and FTIR were used to investicate structure and composition variations of the samples. All samples were found to have a cubie spinel structure. TEM was used to study morphological variations. The results indicate that the average particle sizes are between 29-35 nm. B-H hysteresis measurement was called out at room temperature under field of 5 kOe and this measurement with the increase of Co concentration fields the monotonic increase of saturation magnetization (Ms) and coercive field (lie ). Ferrites with such behavior are important for magnetic recording media, microwave applications, environment and medical biology [1-3]. In view of this, we have studied the various properties of Co doped Ni ferrite.